Work Competency and Professionalism in Creating Organizational Culture - Gunawan, Heri; Utama, Zahera Mega; Marwan, Jubery (Universitas prof. Dr. Moestopo (Beragama), 2026)
This study aims to examine the role of work competency in mediating the relationship between work professionalism and organizational culture. A quantitative cross-sectional explanatory design was employed to test the proposed relationships. The study was conducted at the Secretariat General of the House of Representatives of the Republic of Indonesia, involving 120 employees selected using a census sampling technique. Data were collected through structured questionnaires and analyzed using path analysis, supported by validity, reliability, and normality testing. The results indicate that work professionalism has a significant positive effect on work competency and organizational culture, while work competency also significantly influences organizational culture. Furthermore, work competency partially mediates the relationship between work professionalism and organizational culture, indicating that professionalism affects organizational culture both directly and indirectly through competency development. These findings contribute to the theoretical understanding of human resource management by confirming the role of competency as a key mechanism linking professionalism to organizational outcomes. Practically, the study suggests that organizations should not only promote professional behavior but also strengthen employee competencies through continuous development programs to foster a more effective and sustainable organizational culture